Risque inondation dans le Grand Paris : la résilience est-elle un concept opératoire ? - Alexandre Brun; Frédéric Gache (VertigO)
Great Paris may be affected by a flood of the Seine and Marne rivers. Flooding (such as January 1910) could reduce the economic competitiveness of the French capital for several months. The consequences of flooding are not confined to some parts, banks of the Seine, of Paris : the whole city is actually at risk of flooding. Transport networks and energy are particularly vulnerable. Furthermore, reservoir-dams and dikes that were built upstream of Paris does not protect the capital against an exceptional flood. This is why the concept of urban flood resilience appears as a new alternative for local political management of flood risks, yet very focused on hydraulic protection against floods (dams, dikes, etc.). Nevertheless, conurbation strategy based on resilience implies acceptance of risk and obviously anticipation, especially in terms of planning. However, the concept of resilience, now highly developed in geography and risk analysis, is still unknown to practitioners. Also, Building professionals are unfamiliar with the risk of flooding. They often reduced it to a technical problem. Architects are more aware than in the past, but they have difficulty to conciliate this issue with the priorities of building planners (housing, transport...), while many mutable properties are located in the Grand Paris's flood-risk areas.